Large cross-section blast chamber: design and experimental characterization. (23rd July 2021) - Mejía-Alvarez, Ricardo; Kerwin, Joseph; Vidhate, Suhas; Sandherr, Paul; Patton, Evan; Dávila-Montero, Bianca; Yucesoy, Atacan; Willis, Adam
Abstract: This study shows the basic design and experimental characterization of the advanced blast chamber at Michigan State University. This facility is a large cross-section explosively-driven blast chamber. The cross-section of the facility is 2.03 m × 2.03 m, and the length of its tunnel is 5.5 m. This relatively short length was made possible by introducing a new driver design shaped like a pair of logarithmic spirals with a coincident focus. The experimental characterization of the facility demonstrates that this driver design produces blast fronts with very low curvature, and overpressure durations as short as ∼1.2 ms. Since this was the initial characterization of the facility, the maximum overpressure considered was ∼144 kPa. This facility was conceived to perform studies of blast-induced traumatic brain injury based on full-size models of the human body or large animal models. Its large cross section ensures that area blockage is within permissible values, and its driver design ensures short overpressure durations typical of battle field blast events.